2022
DOI: 10.5195/ijms.2022.1773
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Effects of Third-Dose Moderna Vaccination for Healthcare Workers of Udayana University Hospital, Bali, Indonesia

Abstract: ABSTRACT. Background Since its first sighting in China at the end of 2019, COVID-19 had spread rapidly around the world, with no exception, to Indonesia. World Health Organization officially declared COVID-19 as a pandemic in March 2020. COVID-19 causes severe symptoms for those immunocompromised, making it an urgent matter to end the pandemic as soon as possible. In only 1 year since COVID-19 was found, the world has successfully developed COVID-19 vaccines which experts believe may bring an end … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The study conducted by Zare in Iran [23] revealed that Pain and tenderness at the injection site, fever, and muscle pain are the most common side effect and this coincides with all the studies around the world that have been conducted so far among healthcare staff, which con rmed that the vaccine is safe and has no serious side effects. A study conducted among healthcare workers who received the third dose of mRNA vaccine in Indonesia also recorded the same Adverse which were local pain, fever, weakness/fatigue, excessive sleepiness, dizziness, headache, nausea/vomiting, excessive hungriness and local erythema [24]. Additionally, according to a study conducted in Egypt, 91.3% of healthcare professionals encounter negative side effects from the vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…The study conducted by Zare in Iran [23] revealed that Pain and tenderness at the injection site, fever, and muscle pain are the most common side effect and this coincides with all the studies around the world that have been conducted so far among healthcare staff, which con rmed that the vaccine is safe and has no serious side effects. A study conducted among healthcare workers who received the third dose of mRNA vaccine in Indonesia also recorded the same Adverse which were local pain, fever, weakness/fatigue, excessive sleepiness, dizziness, headache, nausea/vomiting, excessive hungriness and local erythema [24]. Additionally, according to a study conducted in Egypt, 91.3% of healthcare professionals encounter negative side effects from the vaccine.…”
Section: Discussionmentioning
confidence: 99%